2009
DOI: 10.1111/j.1600-079x.2008.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin applied to cucumber (Cucumis sativus L.) seeds improves germination during chilling stress

Abstract: The relationship between germination and melatonin applied during osmo- and hydropriming was studied in cucumber seeds. The proportion of nuclei with different DNA contents, the mean ploidy and the (2C + 4C = 8C)/2C ratio in unprimed and primed, dry and imbibed at 10 degrees C seeds were established by flow cytometry. Thiobarbituric acid reactive substances and protein oxidation were also estimated. Melatonin and indole-3-acetic acid (IAA) concentrations in the seeds were determined using high-performance liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
186
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(199 citation statements)
references
References 44 publications
12
186
0
1
Order By: Relevance
“…In our study, IAA would take central effect for HG35, but ABA would take central effect for JM22 during drought regulation process due to different drought tolerances. Melatonin concentrations applied exert contrasting roles such as stimulatory effect or inhibitory one in different organs and wheat cultivars (Chen et al, 2009;Posmyk et al, 2009). In the present experiment, our results on different melatonin concentrations were also shown to be consistent with previous reports.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our study, IAA would take central effect for HG35, but ABA would take central effect for JM22 during drought regulation process due to different drought tolerances. Melatonin concentrations applied exert contrasting roles such as stimulatory effect or inhibitory one in different organs and wheat cultivars (Chen et al, 2009;Posmyk et al, 2009). In the present experiment, our results on different melatonin concentrations were also shown to be consistent with previous reports.…”
Section: Discussionsupporting
confidence: 82%
“…Fresh leaf and root samples (0.5 g) were measured based on the description of Prochazkova et al (2001). Samples were homogenised in precool acetone (1:1) with a little quartz sand.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Melatonin applied to cucumber (Cucumis sativus L.) seeds improves germination during chilling stress. 56 Recently, Zhao et al 57 reported that melatonin improves the survival of cryopreserved callus of Rhodiola crenulata. The survival rate of the cryopreserved callus increased when the callus was pretreated with 0.1 μM melatonin.…”
Section: Influence Of Cold Stress On Secondary Metabolitesmentioning
confidence: 99%
“…Many researchers have described the protective role of MEL against environmental stresses, such as heavy metals [4,8], cold [9,10], UV-B radiation [11] or salt stress [12]. Antioxidant activity of MEL seems to participate in: (i) the direct scavenging of free radicals, (ii) stimulation of antioxidant enzymes, (iii) augmentation of the activities of other antioxidants, (iv) protection of antioxidant enzymes against oxidative damage, or (v) an increase in the efficiency of the mitochondrial electron transport chain, thereby lowering electron leakage and the generation of free radicals [6].…”
Section: Introductionmentioning
confidence: 99%